2020
DOI: 10.1097/mpg.0000000000002858
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Parents of Children With Biliary Atresia

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
7
0
2
Order By: Relevance
“…Previously, we investigated the QoL of parents of children with BA who already reached school age. [10] We speculate that, over years, parents get accustomed with the chronic disease of their child, resulting in lower levels of anxiety and stress.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previously, we investigated the QoL of parents of children with BA who already reached school age. [10] We speculate that, over years, parents get accustomed with the chronic disease of their child, resulting in lower levels of anxiety and stress.…”
Section: Discussionmentioning
confidence: 97%
“…Anxiety symptoms, as perceived by mothers, significantly decreased from 48 during KPE hospitalization to 37 after 2-3 years of follow-up (Z=-2.29, p=0.02, n=10). Stress levels in mothers significantly decreased from 18 [6-30] at 1-2 months after KPE to 13 [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] after 2-3 years of follow-up (Z=-2.51, p=0.01, n=11). In mothers, psychological QoL significantly decreased between 1-2 months after KPE and when the child reached the age of 2-3 years (Z=-2.56, p=0.01, n=10).…”
Section: Change In Psychosocial Outcomes Over Timementioning
confidence: 99%
See 1 more Smart Citation
“…Liang et al [ 5 ] also observed that having other medical conditions impacted negatively on the HRQOL; an additional factor that impacted the HRQOL was the parents’ knowledge of LT [ 5 ]. In general, HRQOL of parents of children with BA was adversely affected [ 6 ]; Wong et al [ 7 ] performed similar analyses and noted that HRQOL scores did not differ in general between those with a native liver and those post LT.…”
Section: Health Status Of Survivorsmentioning
confidence: 99%
“…Due to the lack of effective coping skills, parents may experience negative psychological symptoms, such as anxiety and depression. 10 Previous studies have shown that mothers' negative emotions can affect infants and lead to acute and chronic diseases. [11][12][13] These negative emotions also have sustained adverse effects on the psychological and cognitive ability of their offspring, which may lead to social dysfunction and behavioral problems.…”
Section: E108mentioning
confidence: 99%